RASAL3 Is a Putative RasGAP Modulating Inflammatory Response by Neutrophils - Saito, Suguru; Cao, Duo-Yao; Victor, Aaron R.; Peng, Zhenzi; Wu, Hui-Ya; Okwan-Duodu, Derick (Frontiers in Immunology, 2021)
As first responder cells in host defense, neutrophils must be carefully regulated to prevent collateral tissue injury. However, the intracellular events that titrate the neutrophil's response to inflammatory stimuli remain poorly understood. As a molecular switch, Ras activity is tightly regulated by Ras GTPase activating proteins (RasGAP) to maintain cellular active-inactive states. Here, we show that RASAL3, a RasGAP, is highly expressed in neutrophils and that its expression is upregulated by exogenous stimuli in neutrophils. RASAL3 deficiency triggers augmented neutrophil responses and enhanced immune activation in acute inflammatory conditions. Consequently, mice lacking RASAL3 (RASAL3-KO) demonstrate accelerated mortality in a septic shock model via induction of severe organ damage and hyperinflammatory response. The excessive neutrophilic hyperinflammation and increased mortality were recapitulated in a mouse model of sickle cell disease, which we found to have low neutrophil RASAL3 expression upon LPS activation. Thus, RASAL3 functions as a RasGAP that negatively regulates the cellular activity of neutrophils to modulate the inflammatory response. These results demonstrate that RASAL3 could serve as a therapeutic target to regulate excessive inflammation in sepsis and many inflammatory disease states.